Accuracy of prostate cancer screening recommendations for high‐risk populations on YouTube and TikTok. Issue 2 (8th November 2022) - Abramson, Max; Feiertag, Nathan; Javidi, Darius; Babar, Mustufa; Loeb, Stacy; Watts, Kara
Abstract: Objectives: This study aimed to evaluate content quality and racial/ethnic representation, particularly of high‐risk cohorts, of prostate cancer screening videos on YouTube (YT) and TikTok (TK). Materials and Methods: The top 50 videos populated for the search term 'prostate cancer screening' on YT and TK that met inclusion criteria were retrieved in a cache‐cleared browser. Three reviewers analysed all videos using validated criteria for the quality of consumer health information (DISCERN and Patient Education Materials Assessment Tool [PEMAT]). High quality was defined as follows: DISCERN ≥ 4, PEMAT understandability ≥75% and PEMAT actionability ≥75%. A 5‐point Likert scale was used to demonstrate the level of misinformation compared to American Urological Association and National Comprehensive Cancer Network guidelines. Perceived race and ethnicity of people in the videos were assessed by consensus approach. Results: TK videos were shorter (median 3.7 vs. 0.5 min, p  < 0.001) and had more views per month (5437.5 vs. 19.3, p  = 0.03) than YT videos. Perceived Black and Hispanic representation was present in 10% and 6% of YT videos and 20% and 12% of TK videos, respectively. High‐risk racial/ethnic groups were explicitly discussed in 46% of YT videos and 8% of TK videos. A total of 98% of YT videos and 100% of TK videos had low‐ to moderate‐quality consumer health information, and 88% of YT videos and 100% of TK videos had moderate to high levels of misinformation based on screening guidelines. Conclusions: YT and TK videos about prostate cancer screening are widely viewed but do not provide quality consumer health information. Black and Hispanic men remain under‐represented on both platforms, and high‐risk racial groups were not discussed in most videos despite the importance for screening criteria. The low understandability and actionability, significant misinformation and lack of diversity in online videos support the need for higher quality videos with adequate attention to high‐risk ethnic cohorts.